2020
DOI: 10.1002/ange.202003359
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Promoted Nickel Catalysis: Etherification of Aryl Electrophiles with Alcohols Catalyzed by a NiII‐Aryl Complex

Abstract: A highly effective C−O coupling reaction of (hetero)aryl electrophiles with primary and secondary alcohols is reported. Catalyzed by a NiII‐aryl complex under long‐wave UV (390–395 nm) irradiation in the presence of a soluble amine base without any additional photosensitizer, the reaction enables the etherification of aryl bromides and aryl chlorides as well as sulfonates with a wide range of primary and secondary aliphatic alcohols, affording synthetically important ethers. Intramolecular C−O coupling is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…2C). Furthermore, the combination of equal mole NiBr 2 and Ni(cod) 2 which is assumed to in-situ generate nickel(I) species via comproportionation 33 , didn't improve catalytic activity but gave lower yield compared to NiBr 2 alone as metal source. And we have not observed the electron paramagnetic resonance (EPR) signal of paramagnetic nickel(I) species 25 .…”
Section: Main Textmentioning
confidence: 98%
“…2C). Furthermore, the combination of equal mole NiBr 2 and Ni(cod) 2 which is assumed to in-situ generate nickel(I) species via comproportionation 33 , didn't improve catalytic activity but gave lower yield compared to NiBr 2 alone as metal source. And we have not observed the electron paramagnetic resonance (EPR) signal of paramagnetic nickel(I) species 25 .…”
Section: Main Textmentioning
confidence: 98%
“…While inorganic bases such as K2CO3 were not effective, possibly due to the precipitation of halides required to stabilize the Ni I intermediate 14 than the loadings used in other Ni-photocatalyzed C-O cross-couplings. 10,11 Moreover, other alcohols such as 1-hexanol and benzyl alcohol could also be employed (Supplementary Table S7, 86-90% product yield). However, the combination of 1a and heterogenous Zn 0 or Mn 0 without light was ineffective in our conditions, likely due to the slow electron transfer kinetics or insufficient generation of the active species during catalysis.…”
Section: Photocatalytic C-o Coupling Reactions Mediated By ( R N3)nicl 2 Complexesmentioning
confidence: 99%
“…In this regard, photoredox/nickel dual catalysis and light-promoted Ni catalysis have emerged as powerful strategies for challenging C-O bond formations. [8][9][10][11] Accordingly, an in-depth mechanistic understanding of Ni-mediated photocatalysis is essential for rational reaction design and optimization. From a mechanistic viewpoint, while the photocatalytic cycle is well-understood, the Ni-mediated redox cycle remains elusive as intermediates in various oxidation states (from Ni 0 to Ni IV ) have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 This observation was expanded to a synthetic protocol for C-O and C-N cross-couplings using UV-light irradiation. 24,25 More recently, pulse radiolysis together with spectroelectrochemistry indicated that Ni 0 /Ni II comproportonation generates a Ni I bipyridyl species that rapidly undergoes oxidative addition with iodobenzene. 21 Moreover, Nocera and coworkers showed that sub-stoichiometric amounts of zinc can be used instead of a photocatalyst and light for C-N and C-O cross-couplings.…”
Section: Main Introductionmentioning
confidence: 99%